Pelatihan dan Implementasi Sistem Pencatatan Akuntansi Digital untuk Pengelolaan Keuangan Jimpitan RT - Tantri Risda Zubaidah; Dewi Sri Rahayu; Putri Amalia Ramadani; Muhammad Andi; Rakhis Regina Tito; Ruri Fadhilah Kurniati (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
Manual jimpitan financial management in RT 03 RW 01 Ngaresrejo Village, Sidoarjo Regency faces problems of inaccurate recording and lack of transparency to residents. The purpose of this community service is to improve the efficiency and transparency of jimpitan financial management through training and implementation of a digital accounting recording system. The method used is the Asset-Based Community Development (ABCD) method and includes several stages such as identifying needs, preparing training materials, implementing workshops, and direct assistance in using the system. The results of this program show that RT administrators can use the digital system well, increasing the accuracy and transparency of financial reports. The main contribution of this program is the application of digital technology in community financial management, which has the potential to be a model for other RTs. This innovation not only simplifies the administrative process but also strengthens community trust in fund management.